Galectin-8 Enhances T cell Response by Promotion of Antigen Internalization and Processing - Prato, Cecilia Arahi (2020)
Galectin-8 (Gal-8) is a mammalian lectin endowed with immunostimulatory ability. In the present work, we demonstrate that Gal-8-glycan interactions on the surface of antigen-presenting cells (APCs) promote antigen binding and internalization, independently from antigen nature. Both Gal-8 and antigen were together internalized and localized in early endosomes. Interestingly, antigen processing by APCs was also accelerated in the presence of Gal-8 as a separate mechanism, distinct from the increased antigen internalization. Moreover, APCs pulsed together with antigen and Gal-8 were able to activate cognate CD4+ T cells more efficiently than those pulsed with antigen alone. This enhanced antigen presentation was still evident in the absence of costimulatory signals and APCs-derived soluble mediators. Therefore, our results provide evidence for as yet unrecognized mechanism by which Gal-8 stimulates the elicitation of the immune response in a lectin-dependent manner, by inducing antigen uptake and processing upon lattice formation at APCs surface.